2015
DOI: 10.1589/jpts.27.289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abduction and external rotation of the hip joint on muscle onset time during prone hip extension with knee flexion

Abstract: [Purpose] This study investigated the effect of hip position on muscle onset time during prone hip extension with knee flexion. [Subjects] The study included 21 healthy male volunteers. [Methods] Muscle onset times of the right gluteus maximus, right hamstrings, bilateral lumbar erector spinae, and bilateral lumbar multifidus were measured using surface electromyography during right hip extension with knee flexion in the prone position. Measurements were made with the hip in 3 positions: (1) neutral, (2) abduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Concerning the patterns in healthy individuals, there was moderate evidence [26,27] and weak evidence [13,17,24,25] that the HAM and ES muscles were almost simultaneously activated before the onset of the leg movement during PHE, while they exhibited inconsistent and variable patterns in the remaining studies [16,18,22,23,28]. GM was significantly delayed and constituted the last muscle to activate during PHE in all studies which examined healthy participants.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Concerning the patterns in healthy individuals, there was moderate evidence [26,27] and weak evidence [13,17,24,25] that the HAM and ES muscles were almost simultaneously activated before the onset of the leg movement during PHE, while they exhibited inconsistent and variable patterns in the remaining studies [16,18,22,23,28]. GM was significantly delayed and constituted the last muscle to activate during PHE in all studies which examined healthy participants.…”
Section: Discussionmentioning
confidence: 98%
“…Although most of the studies in this review used PHE test starting from neutral to maximum hyperextension, in 2 studies the participants started the test with hip in 30° flexion to maximum extension [16,28]. These papers suggested that those subjects with a limited end range of extension would be performing trunk hyperextension instead of hip extension during prone leg lifting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations